Polymer nanoparticles: adsorption and desorption of the weedkiller Tebuthiuron turned to green chemistry - de Oliveira, Patricia Neves; Andrade, Romulo Davi Albuquerque (Orbital: The Electronic Journal of Chemistry, 2018)
The herbicide Tebuthiuron is a major responsible for controlling and combating weeds in sugarcane crops, but its use poses serious environmental risks. In order to reduce the amount of product used, a study of herbicide anchoring in nanospheres and controlled release was performed, observing factors such as conductivity and pH variation. The results of conductimetric titrations and UV analysis in the visible region showed the efficiency of the chitosan nanospheres in the controlled release process of the anchored herbicide. DOI: http://dx.doi.org/10.17807/orbital.v10i5.1136